Fracking, Coal, and Air Quality - Johnsen, Reid; LaRiviere, Jacob; Wolff, Hendrik (Journal of the Association of Environmental and Resource Economists, 2019)
This paper estimates indirect benefits of improved air quality induced by hydraulic fracturing, or “fracking” in the continental United States. The recent increase in natural gas supply led to displacement of coal-fired electricity by cleaner natural gas-fired generation. Using detailed spatial panel data comprising the near universe of air quality monitors merged with US power plant locations, we find that coal generation decreased by 28% attributable to lower natural gas prices. Using an IV identification strategy to isolate fracking’s impact on natural gas prices, we identify a 4% decrease in average PM2.5 levels due to decreased coal generation. These benefits vary geographically; air pollution levels decreased most in parts of Alabama by 35%. Back of the envelope calculations imply accumulated health benefits of roughly 17 billion annually.